Optimalisasi Pembelajaran Realistik melalui Pelatihan Pemanfaatan Penggunaan Media Kulit Jeruk dalam Pembelajaran Matematika Siswa Kelas VIII di SMP Al Wildan Islamic School - Wieka Septiyana; Ramzil Huda Zarista; Suyanto; Ati Adi Yanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This service activity aims to improve students' mathematical abilities in learning mathematics through training on the use of orange peel media in realistic mathematics learning. Technically, the implementation of the designed training activities is as follows: 1) Planning. At this stage, the team identified problems that occurred by observing the school and interviewing students directly. This aims to find out students' opinions and the obstacles they face while participating in class learning. From the results of these interviews, the team concluded that the topic of discussion that many students had problems with was the concept of building space. 2) Preparation. The team held discussions with teachers at the service site to determine the subjects involved and confirm the prerequisite material. Apart from that, tasks are distributed to teams so that learning can run optimally and be enjoyable. 3) Implementation. The implementation of the service was welcomed by the Principal and Mathematics Teachers. Mathematics teachers are also involved in guiding students using orange peel media when the service is carried out. 4) Evaluation and Reporting. At this stage, the team carries out an evaluation after the service activities are completed and compiles them into a service report for publication.